2018
DOI: 10.1093/beheco/ary067
|View full text |Cite
|
Sign up to set email alerts
|

Elevation-related difference in serial reversal learning ability in a nonscatter hoarding passerine

Abstract: Environments characterized by scarce and variable food supply, termed "harsh environments," have been hypothesized to favor cognitive abilities that aid an animal in finding food, remembering where it is located, or predicting its availability. Most studies of the "harsh environment" hypothesis have found that scatter hoarders from harsher environments have better spatial memory abilities, but few studies have looked at this hypothesis in nonscatter hoarders. Here, we present the first comparison of performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…[ 63 ] P. gambelli spatial memory, reversal learning altitude mixed (no effect and negative) not tested Hermer et al . [ 64 ] great tit, Parus major reversal learning altitude mixed (no effect and negative) not tested …”
Section: Intraspecific Evidence For the Social Intelligence Hypothesimentioning
confidence: 99%
“…[ 63 ] P. gambelli spatial memory, reversal learning altitude mixed (no effect and negative) not tested Hermer et al . [ 64 ] great tit, Parus major reversal learning altitude mixed (no effect and negative) not tested …”
Section: Intraspecific Evidence For the Social Intelligence Hypothesimentioning
confidence: 99%
“…Instead, and in accordance with a lack of spatial memory accuracy differences, we found no difference between high and low elevation birds in their proactive interference. Interestingly, in a previous study on great tits collected from the same population, we found that birds from high elevation performed less accurately on a serial spatial reversal learning task than low elevation great tits 16 . We surmised that one potential explanation for this result was that spatial memory may have been more accurate in high elevation great tits, which would lead to greater spatial proactive interference and worse reversal performance, as found in the scatter hoarding system 21 , 41 .…”
Section: Discussionmentioning
confidence: 52%
“…A first possible explanation is that the two elevations we sampled do not differ enough in harshness. However, this is unlikely as previous studies that sampled birds from the same population and elevations found a significant cognitive difference (i.e., laboratory test of serial reversal learning 16 ), as well as differences in breeding phenology 52 and parental care 45 between high and low elevation birds. Therefore, some environmental difference between high and low elevations seems to be driving behavioural differences.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is growing evidence to support this from comparative studies of primates (review in Rosati, 2017), birds (Freas et al, 2012, Sonnenberg et al, 2019, bats and rodents (review in Harvey and Krebs, 1990). However, a recent study highlighted the need for a clearer definition of what constitutes environmental 'harshness' (Hermer et al, 2018). Based on the results of this study, we propose that environmental harshness could be expanded beyond the spatio-temporal complexity of food resources to include landscape complexity.…”
Section: Discussionmentioning
confidence: 72%